Growth differentiation factor 15 aggravates sepsis-induced cognitive and memory impairments by promoting microglial inflammatory responses and phagocytosis - Lijiao Chen; Shiyuan Luo; Ting Liu; Zhewei Shuai; Yifan Song; Qianzi Yang; Ying Wang; Hongjun Huang; Yan Luo (Journal of Neuroinflammation)
Abstract Background Sepsis-associated encephalopathy (SAE) is a severe neurological condition caused by sepsis, and presents with symptoms ranging from delirium and coma to long-term cognitive dysfunction. SAE is acknowledged as a widespread brain impairment characterized by the activation of microglia. However, the specific pathological mechanisms that drive this activation are still not clearly understood. Growth differentiation factor 15 (GDF15) levels have been noted to be considerably increased in patients with sepsis, where they are linked to disease severity and can independently predict short- and long-term mortality risk. Serum levels of GDF15 have also been negatively associated with gray matter volume and predict cognitive impairment in older individuals. However, the impact of GDF15 on sepsis-induced cognitive and memory impairments, as well as the mechanisms behind these effects, are poorly understood. Methods To examine the role of GDF15 in SAE, a sepsis model was created in adult C57BL/6J mice using intraperitoneal administration of lipopolysaccharide (LPS). GDF15 levels in plasma and cerebrospinal fluid were measured by ELISA. The anti-GDF15 monoclonal antibody ponsegromab was injected intracerebroventricularly before modeling, and cognitive and memory functions of the septic mice were assessed using fear-conditioning and novel object recognition tests. Microglial activation and phagocytosis were evaluated using immunofluorescence and Golgi staining. Additionally, an in vitro investigation of LPS-stimulated microglia was conducted to evaluate the impacts of GDF15 on inflammatory cytokine productions and microglial phagocytic activity. Mechanisms were explored using RNA sequencing, qPCR, western blotting, flow cytometry, and immunofluorescence assays. Results In the cerebrospinal fluid of septic mice, levels of GDF15 were notably elevated after intraperitoneal injection of LPS. Lateral ventricular injection of the anti-GDF15 antibody alleviated both cognitive and memory impairment in the septic mice, together with microglial activation and phagocytosis in the hippocampus, thereby protecting against synaptic loss. Conclusion The levels of GDF15 were elevated in the brains of septic mice. Targeting GDF15 with an anti-GDF15 antibody was found to improve sepsis-induced cognitive and memory impairment by reducing the microglial inflammatory response and phagocytosis. These results indicate that GDF15 could serve as an important therapeutic target for treating SAE.